4-Amino-N-(4,6-dimethylpyrimidin-2-yl)benzenesulfonamide–1,4-diazabicyclo[2.2.2]octane (2/1) - Hadi D. Arman; Trupta Kaulgud; Edward R. T. Tiekink (Acta Crystallographica Section E, 2013)
The asymmetric unit of the title co-crystal, C12H14N4O2S·0.5C6H12N2, comprises the sulfonamide molecule and half a molecule of 1,4-diazabicyclo[2.2.2]octane (DABCO), the latter being disposed about a crystallographic twofold rotation axis. In the sulfonamide molecule, the aromatic rings are almost perpendicular to one another [dihedral angle = 75.01 (8)°]. In the crystal, molecules are connected into a three-molecule aggregate via amide–DABCO N—H...N hydrogen bonds, and these are connected into a three-dimensional architecture via amino–DABCO N—H...O and amino-pyrimidine N—H...N hydrogen bonds.